4CPS-261 Grade of chronicity in nonagenarians: can we compare number and type of drug interventions?. (2nd March 2018) - Roig, S Ortonobes; Comas, G Puig; Marzo, MA Villarino; Monte, R Comet; Albors, P Miralles; Contel, A Perez; Molas, G; Gómez-Valent, M
Abstract : Background: Impaired functionality, cognitive decline, comorbidity and polypharmacy in nonagenarians increase mortality risks associated with age. Polypharmacy (>4 chronic drugs) in elderly people is related to an increase in drug-related problems (DRP) and worse health outcomes due to potentially inappropriate prescriptions (PIP). To optimise medical care for chronic patients, our healthcare system stratifies chronic patients according to their grade of chronicity in chronic complex patients (CCP) or CCP with advance chronic disease (CCP-ACD). Purpose: To evaluate the differences related to functionality, cognition, polypharmacy and pharmacist interventions due to DRP (PI-DRP) regarding the grade of chronicity. Material and methods: We included ≥90 years-old patients with polypharmacy discharged between January and June of 2017 from an Acute Geriatric Unit (81 beds) of a Geriatric Healthcare Centre. Registered variables: age, sex, grade of chronicity, Barthel Index and Pfeiffer Test before admission. Number of chronic drug/patient, number of PIP/patient and chronic benzodiazepines use before admission, and PI-DRP. Data are presented as median (Q1–Q3). We use Fisher's exact test for qualitative and the Mann–Whitney U test and the Wilcoxon signed-rank test for quantitative data. Statistical analysis was performed with Stata 13. Results: One hundred and eighteen patients included: 83 CCP and 35 CCP-ACD. Differences between CCP and CCP-ACD: age 92 (90–94) vs 94 (91–95), p=0.029. Females 58 (69.9%) vs 20 (57.1%), p=0.205. Data at admission: Barthel Index 55 (40–80) vs 40 (20–60), p=0.010; Pfeiffer Test three (1–6) vs four (2–8), p=0.432. Chronic drugs/patient 10 (8–12) vs 10 (7–14), p=0.972. Average of PIP/patient 1.2 (±0.88) vs 0.86 (±0.85), p=0.049; chronic benzodiazepines use 30 (36.1%) vs 6 (17.1%), p=0.050. PI-DRP: indication 10 (12%) vs 2 (5.7%) patients, p=0.506; effectivity 11 (13.3%) vs five (14.3), p=0.881; safety one (1.2%) vs four (11.4%), p=0.027; advice to nursing three (3.6%) vs two (5.7%), p=0.632; others 11 (13.3%) vs five (14.3%), p=0.881. Conclusion: CCP–ACD group are older than CCP, and have worse results in functional status without differences in cognitive function. Although the number of chronic drugs prescribed between the two groups are similar, CCP–ACD have significantly less PIP and use less chronic benzodiazepines than CCP. The major pharmaceutical interventions have been those of safety in the CCP–ACD group. References and/or Acknowledgements: All medical and nursing staff of Geriatric-Healthcare Centre. No conflict of interest